2009
DOI: 10.1378/chest.08-2568
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Children

Abstract: Background:The obesity epidemic has prompted remarkable changes in the proportion of obese children who are referred for habitual snoring. However, the contribution of obesity to adenotonsillar hypertrophy remains undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(58 citation statements)
references
References 47 publications
4
51
1
2
Order By: Relevance
“…Furthermore, the apnea–hypopnea index (AHI) has not been shown to directly correlate with airway volume,7 and the coefficients of correlation between AHI and adenotonsillar size have been found to be usually relatively weak, albeit statistically significant,9,18 suggesting that other factors feature in the pathophysiology of pediatric OSA. The concept of airway collapsibility has thus been proposed to provide a more comprehensive and unified approach to this issue.…”
Section: Pathophysiology Of Osamentioning
confidence: 99%
“…Furthermore, the apnea–hypopnea index (AHI) has not been shown to directly correlate with airway volume,7 and the coefficients of correlation between AHI and adenotonsillar size have been found to be usually relatively weak, albeit statistically significant,9,18 suggesting that other factors feature in the pathophysiology of pediatric OSA. The concept of airway collapsibility has thus been proposed to provide a more comprehensive and unified approach to this issue.…”
Section: Pathophysiology Of Osamentioning
confidence: 99%
“…Therefore, the magnitude of adenotonsillar effects on childhood OSA may be altered by age and obesity [14,15]. Tagaya et al [14] asserted that the correlation between adenoid size and OSA is more prominent in preschool children than in school-aged children.…”
Section: Introductionmentioning
confidence: 99%
“…Tagaya et al [14] asserted that the correlation between adenoid size and OSA is more prominent in preschool children than in school-aged children. Dayyat et al [15] reported a modest association between adenotonsillar sum scores and apnea index in non-obese children, but not in obese children. However, the relationships between adenotonsillar size and OSA in detailed age groups, and the respective effect of adenoid and tonsil size on OSA in obese and non-obese children, have not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The basic pathological changes of obesity and OSAHS are closely related to insulin resistance and the metabolic syndrome of dyslipidemia [24,25]. OSAHS could be induced by the oxidative stress caused by repeatedly hypoxia and re-oxygenation during sleep.…”
Section: Discussionmentioning
confidence: 99%